Web crippling strength of cold-formed stainless-steel lipped channels with web perforations under end-two-flange loading. Issue 12 (December 2017) - Yousefi, Amir M; Uzzaman, Asraf; Lim, James BP; Clifton, G Charles; Young, Ben
This article presents a finite element investigation into the web crippling strength of cold-formed stainless-steel lipped channels with circular web perforations under end-two-flange loading. The cases of web openings located both centred and offset to the load bearing plates are considered. In order to take into account the influence of the circular web openings, a parametric study involving 2190 finite element analyses was performed, covering duplex EN 1.4462, austenitic EN 1.4404 and ferritic EN 1.4003 stainless-steel grades; from the results of the parametric study, strength reduction factor equations are determined. The strength reduction factor equations are first compared to equations recently proposed for cold-formed carbon-steel lipped channels. It is demonstrated that the strength reduction factor equations proposed for cold-formed carbon steel are conservative for the stainless-steel grades by up to 10%. New coefficients for web crippling strength reduction factor equations are then proposed that can be applied to all three stainless-steel grades.